MINIMALLY INVASIVE LAPAROSCOPIC ESOPHAGECTOMY VS. TRANSHIATAL OPEN ESOPHAGECTOMY IN ACHALASIA: A RANDOMIZED STUDY - FONTAN,Alberto Jorge Albuquerque (2018)
ABSTRACT Background: Open and laparoscopic trans-hiatal esophagectomy has been successfully performed in the treatment of megaesophagus. However, there are no randomized studies to differentiate them in their results. Aim: To compare the results of minimally invasive laparoscopic esophagectomy (EMIL) vs. open trans-hiatal esophagectomy (ETHA) in advanced megaesophagus. Method: A total of 30 patients were randomized, 15 of them in each group - EMIL and ETHA. The studied variables were dysphagia score before and after the operation at 24-months follow-up; pain score in the immediate postoperative period and at hospital discharge; complications of the procedure, comparing each group. Were also studied: surgical time in minutes, transfusion of blood products, length of hospital stay, mortality and follow-up time. Results: ETHA group comprised eight men and seven women; in the EMIL group, four women and 11 men. The median age in the ETHA group was 47.2 (29-68) years, and in the EMIL group of 44.13 (20-67) years. Mean follow-up time was 33 months, with one death in each group, both by fatal aspiration. There was no statistically significant difference between the EMIL vs. ETHA scores for dysphagia, pain and in-hospital complications. The same was true for surgical time, transfusion of blood products and hospital stay. Conclusion: There was no difference between EMIL and ETHA in all the studied variables, thus allowing them to be considered equivalent.